Impacts of Mergers and Acquisitions on Acquirer Banks’ Performance - Burhan Ali Shah; Niaz Khan (Australasian Accounting, Business and Finance Journal, 2017)
This study investigates the effects of mergers and acquisitions (M & A) on the operating performance of the acquirer banks in Pakistan. For this purpose, a sample of 18 transactions, involving acquirer banks, listed on the Karachi Stock Exchange, is used. The Financial Ratio Analysis (FRA) is used to determine the effects of M & A. The significance of change in the operating performances is tested through a paired sample t-test. The results indicate deterioration in the performances of the acquirer banks in the post-merger period.
Keywords: M & A; mergers and acquisitions; financial ratio analysis; ratios; profitability; liquidity; capital adequacy; performance; Pakistan